The Design of Alignment Horizontal Using Indonesia Highway Design Standard: A Case of Jalan Babat – Tapen, East Java - Ilham Rafid Andito; Andri Irfan Rifai; Adinda Fajarika Akhir (International Journal Labs, 2022)
Horizontal alignment is included in the aspect of the geometric design of the road. Jalan Babat – Tapen in Jombang, East Java, is planned to have three horizontal alignments. This design aims to connect Jalan Babat and Jalan Tapen to shorten the travel time for the surrounding community's needs. This research uses the Bina Marga method, which refers to the Highway Design Standard of Indonesia 2021. First, road traffic data is obtained from the google earth application. The global mapper is then processed in AutoCAD to determine the coordinates of the road trace and the location of horizontal alignment. Then the data obtained is processed by referring to the Bina Marga method to design horizontal alignment. Jalan Tapen – Babat is a Secondary SJJ (Urban Road), Secondary Collector, and medium road, and the minor type of road 2/2 is not separate (TT). It has a flat terrain in design with a planned speed of 40 km / h. Three horizontal alignments with Spiral-Circle-Spiral (SCS) type, the first horizontal alignment is at STA 0+700 – 0+864, the second horizontal alignment is at STA 1+383 – 1+558, and the third horizontal alignment is at STA 2+132 – 2+304.